Chronic obstructive pulmonary disease is associated with an increased risk of herpes zoster: A retrospective United States claims database analysis. (22nd November 2022) - Thompson‐Leduc, Philippe; Ghaswalla, Parinaz; Cheng, Wendy Y.; Wang, Min‐Jung; Bogart, Michael; Patterson, Brandon J.; Duh, Mei Sheng; Park, Suna; Yawn, Barbara P.
Abstract: Chronic obstructive pulmonary disease (COPD) has been reported as a potential risk factor for developing herpes zoster (HZ). We aimed at comparing incidence rates of HZ between people with versus without COPD in the US. This retrospective cohort study used data from Optum's de‐identified Clinformatics Data Mart database from 1/1/2013 through 12/31/2018. We identified two cohorts of people ≥40 years without prior HZ, HZ vaccination, postherpetic neuralgia (PHN) or HZ ophthalmicus: those with (COPD+) and those without (COPD−) a COPD diagnosis. Adjusted incidence rate ratios (aIRRs) of HZ and PHN were calculated using generalized linear models, controlling for the propensity score of being diagnosed with COPD and relevant demographic and clinical characteristics. People in the COPD+ cohort ( n  = 161 970) were considerably older, had more comorbidities and were more likely to use corticosteroids than those in the COPD− cohort ( n  = 9 643 522). The incidence rate of HZ was 5.7‐fold higher in the COPD+ versus COPD− cohorts (13.0 vs. 2.3 per 1000 person‐years [PY]; aIRR, 2.77; 95% confidence interval [CI], 2.69 to 2.85; P  < 0.001). The unadjusted incidence rate of PHN was 1.7‐fold higher in the COPD+/HZ+ versus COPD−/HZ+ cohort (64.8 vs. 37.1 per 1000 PY), but not after adjustment (aIRR, 1.07; 95% CI, 0.79 to 1.45). HZ and PHN incidence rates increased with age. After adjustment, COPD+ adults had a 2.8‐fold increased risk of developing HZ. These results may help to increase awareness about potential risk factors for HZ and highlight the need for vaccination among those at increased risk. Abstract : This study reviewed 2013–2018 US insurance claims data to compare the incidence rates of herpes zoster among people 40 years and older with and without chronic obstructive pulmonary disease. Adjusting for baseline demographics and clinical characteristics, this study found that people with chronic obstructive pulmonary disease were nearly three times more likely to develop herpes zoster than those without.